1985
DOI: 10.1037/0021-9010.70.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in nonverbal and verbal communication with bosses, peers, and subordinates.

Abstract: Relatively little is known about differences in either the nonverbal or verbal behavior of male and female managers. The present study examines both nonverbal and verbal behavior of male and female master's in business administration (MBA) candidates as they speak on the telephone to their boss, peer, and subordinate. Ratings of the competence and warmth of their tone of voice and of the transcript of the conversation yielded parallel measures of both nonverbal and verbal channels. A repeated measures analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 30 publications
(27 reference statements)
1
26
0
1
Order By: Relevance
“…Members of devalued groups may seek to convince others of their legitimacy in the socially valued group by downplaying the devalued identity (e.g., avoiding conversations about the devalued identity, avoiding mannerisms that are considered stereotypical of the devalued group). For instance, laboratory studies have suggested that people who expect to be the target of prejudice are more likely to downplay a devalued identity in a simulated performance evaluation, job interview, or social interaction (Kaiser & Miller, 2001;Steckler & Rosenthal, 1985;von Baeyer, Sherk, & Zanna, 1981). Alternatively, they might educate others about the positive attributes of the devalued identity (Bell & Nkomo, 2001;Creed & Scully, 2000;Roberts, 2005).…”
Section: Perceptions Of Identity Devaluationmentioning
confidence: 97%
“…Members of devalued groups may seek to convince others of their legitimacy in the socially valued group by downplaying the devalued identity (e.g., avoiding conversations about the devalued identity, avoiding mannerisms that are considered stereotypical of the devalued group). For instance, laboratory studies have suggested that people who expect to be the target of prejudice are more likely to downplay a devalued identity in a simulated performance evaluation, job interview, or social interaction (Kaiser & Miller, 2001;Steckler & Rosenthal, 1985;von Baeyer, Sherk, & Zanna, 1981). Alternatively, they might educate others about the positive attributes of the devalued identity (Bell & Nkomo, 2001;Creed & Scully, 2000;Roberts, 2005).…”
Section: Perceptions Of Identity Devaluationmentioning
confidence: 97%
“…Compensation involves adapting one's social interaction strategies in an attempt to achieve goals despite the existence of prejudice (Miller & Myers, 1998) by behaving in a socially skillful (Miller et al, 1995;Miller & Rudiger, 1997) or stereotype-disconfirming fashion (Kaiser & Miller, in press). For example, women (but not men) spoke more competently during interactions with employers than during interactions with peers (Steckler & Rosenthal, 1985), and women who believed they would be evaluated by a sexist grader created less feminine impressions on a self-descriptive essay compared to women who did not anticipate sexist graders (Kaiser & Miller, in press). …”
Section: Engagement Copingmentioning
confidence: 98%
“…Ambady et al ( 1 996), Lee ( 1 993). and Steckler and Rosenthal(1985) found that when communicating face threats, men used more strategies when communicating to individuals with more power, but women used more strategies when communicating to individuals with equal power. Two explanations have been offered to explain these effects (Hodgins, Liebeskind, & Schwartz, 1996).…”
Section: Effect Of Power On Verbal Strategiesmentioning
confidence: 98%